Childhood Obesity, Self-Esteem and Health-Related Quality Of Life among Urban Primary Schools Children in Kuching, Sarawak, Malaysia - Lee, Ping Yein; Cheah, W.L; Chang, C.T; Ghazali, S.R (Nutrition Society of Malaysia, 2012)
Introduction: There is limited data on childhood obesity and its impact on children from diverse cultural backgrounds. This study is aimed at determining the association between obesity, self-esteem and health-related quality of life (HRQOL) among Malaysian urban primary school children of different ethnicity. Methods: A cross-sectional study was conducted involving 311 children aged 11- 13 years from primary schools in Kuching, Sarawak. Self-esteem and healthrelated quality of life (HRQOL) were measured using the Lawrence Self-esteem Questionnaire (LAWSEQ) questionnaire and the Paediatric Quality of Life Inventory (PedsQL), respectively. Body weight and height were taken and body mass index for age calculated. Results: The prevalence of overweight and obesity among the children were 18.2% and 15.2% respectively. Parent-proxy and child self-reported PedsQL scores were higher for normal weight children compared to thin and obese children, but lower than overweight children. At the subscale level, only parent-proxy PedsQL scores in psychosocial health and emotional component were significantly different between overweight and obese children (p=0.019, p=0.02). The Self-esteem score was significantly correlated with parent and child PedsQL scores. Although obesity was associated with lower HRQOL among children, both parent and child PedsQL scores among the overweight group were higher than that for the normal weight group. Overweight and obesity did affect quality of life and self-esteem of children in this study, particularly in the areas of psychosocial and emotional health. Conclusion: Policy makers and programme managers should take into consideration the impact of obesity on children and parents in designing intervention programmes.